The future of legal Europe: will we trust in it? : liber amicorum in honour of Wolfgang Heusel - Barrett, Gavin; Rageade, Jean-Philippe; Wallis, Diana; Weil, Heinz (Springer, 2021)
With this Liber Amicorum, around 50 contributors from the legal and judicial professions, from academia and from politics pay tribute to Dr Wolfgang Heusel, the Director of the Academy of European Law (ERA) in Trier from 2000 to 2020. The contributions provide a thorough analysis of some of the most relevant legal and political challenges faced by the European Union, including in the fields of data protection rules, artificial intelligence, the rule of law, human rights protection, institutional reform of the EU and changes in the legal and judicial professions. The book is primarily aimed at postgraduate students, legal practitioners and scholars interested in EU legal matters.
Keywords: Festschrift